Critical Thinking Ability Using STEAM-Based PBL Learning at Junior High School Students - Merri Sri Hartati; Irmaning Rahayu; Kashardi Kashardi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
This research aims to determine whether there are differences in students' critical thinking abilities using STEAM-based Problem Based Learning (PBL) in science learning at SMP Negeri 14 Bengkulu City. The population of this study were all students in class VIII of SMP Negeri 14 Bengkulu City. The sampling technique used Simple Random Sampling with a total sampling of 62 people from 2 classes consisting of 32 students in class VIII.2 and 30 students in class III.4. The type of research used is quasi-experimental. Data collection was carried out using an essay test to measure critical thinking abilities. Data were analyzed using the ANOVA test. The research results show that 1) there are differences in critical thinking abilities using the STEAM-based PBL learning model. Judging from the ANOVA test where a significant value of 0.000 was obtained, it can be concluded that sig <0.05. 2) STEAM-based PjBL learning is more effective in improving students' critical thinking skills compared to conventional ones. Judging from the ANOVA test value, it obtained a significant value of 0.000, so it can be concluded that sig < 0.05 on the BNT test obtained a value of 0.132 > 0.05.